2017
DOI: 10.1177/1066896917750472
|View full text |Cite
|
Sign up to set email alerts
|

A Plasma Cell Myeloma With Post-Therapy Anaplastic Morphology, Osteomyelosclerosis, and Strong Pan-Cytokeratin (AE1/AE3) Expression: A Potential Diagnostic Pitfall

Abstract: Reactive and neoplastic plasma cells can display considerable morphological anaplasia as well as variable immunoreactivity for epithelial markers including epithelial membrane antigen, pan-cytokeratin (panCK) and high-molecular-weight cytokeratin, potentially creating diagnostic dilemmas. We describe the case of a 51-year-old male, previously treated for IgGλ plasma cell myeloma, whose bone marrow biopsy showed focal replacement by sheets of pleomorphic malignant cells and grade 3 myelofibrosis, raising the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…A previous studies showed expression of cytokeratins is a very rare phenomenon in DLBCL (2 of 326, 0.6%) 14 . The staining pattern is similar to previous reports in DLBCL, anaplastic large cell lymphoma, plasma cell myeloma, and plasmablastic lymphoma 13‐19 . Plasma cell myeloma and Hodgkin's lymphoma showed intensive cytoplasmic staining 14 .…”
Section: Discussionsupporting
confidence: 89%
“…A previous studies showed expression of cytokeratins is a very rare phenomenon in DLBCL (2 of 326, 0.6%) 14 . The staining pattern is similar to previous reports in DLBCL, anaplastic large cell lymphoma, plasma cell myeloma, and plasmablastic lymphoma 13‐19 . Plasma cell myeloma and Hodgkin's lymphoma showed intensive cytoplasmic staining 14 .…”
Section: Discussionsupporting
confidence: 89%
“…Myeloma can pose morphological challenges [2]. Small lymphocytic morphology is rare and may carry a better prognosis [3].…”
mentioning
confidence: 99%